2017
DOI: 10.1002/2017gl075797
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Extracellular Carbonic Anhydrase in the Sea Surface Microlayer and Its Effect on Air‐Sea CO2 Exchange

Abstract: This paper describes the quantification of extracellular carbonic anhydrase (eCA) concentrations in the sea surface microlayer (SML), the boundary layer between the ocean and the atmosphere of the Indo-West Pacific. We demonstrated that the SML is enriched with eCA by 1.5 ± 0.7 compared to the mixed underlying water. Enrichment remains up to a wind speed of 7 m s À1 (i.e., under typical oceanic conditions). As eCA catalyzes the interconversion of HCO 3 À and CO 2 , it has been hypothesized that its enrichment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Two recent studies reported total CA concentrations—not activities—on the order of 0.2 nM eCA in the surface waters of the Mediterranean (Mustaffa et al ) and Equatorial Pacific (Mustaffa et al ). These concentrations are > 1000 times higher than the effective BCA concentrations we measured in the subpolar gyre (~ 0.15 pM, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Two recent studies reported total CA concentrations—not activities—on the order of 0.2 nM eCA in the surface waters of the Mediterranean (Mustaffa et al ) and Equatorial Pacific (Mustaffa et al ). These concentrations are > 1000 times higher than the effective BCA concentrations we measured in the subpolar gyre (~ 0.15 pM, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Using the 100× scaling factor described above based on CA/Chl a ratios, our measured CA activity would represent 10–40% of the Zn quota. A scaling factor of 1000×, based on the data of Mustaffa et al (), would imply that CA is responsible for 100–400% of the Zn quota, which is unreasonable given the many other biological demands for Zn (Sunda ; Twining and Baines ). Therefore, we suggest that CA may account for up to 10–40% of the Zn quota in marine plankton assemblages, although this estimate is still speculative.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations